Qualitative indicators for measuring the performance development of selected cities - Mavrič, Jasmina (Naše gospodarstvo, 2014)
Recognizing that cities are becoming generators of economic development and a source of growth for the national economy, researchers are increasingly identifying the stages of development and positioning of cities upon which the adequate preparation of strategic and development guidelines is dependent. The comparison of the level of their development efficiency calls for indicators measuring the performance of cities that are representative and comparable between countries. In the case of medium-sized cities, we consequently have to question the applicability of the methodology and indicators used mostly in cases of large, global cities by internationally recognized institutions. With the established set of qualitative indicators and assistance from a computer program for multiparameter decision-making processes (DEXi), this paper also seeks to compare the performance development of selected European cities.
Keywords: mesta; urbanizacija; regionalna ekonomija; razvoj; uspešnost; merjenje; sustainable development; trajnostni razvoj